DOKTRIN WIRAUSAHA ALA RASÛLULLÂH - Farid Firmansyah (Al-Ihkam: Jurnal Hukum dan Pranata Sosial)
Indonesia face the challenge of economy globalization era that is free trade system that has been agreed by the world. Trade system and free-opened investment becomes global commitment signed by agreement of GATT (General Agreement on Tariffs and Trade) and the form of world trade organization, WTO. Indonesia must be able to prepare human resource to face this global challenge. Indonesian government needs young generation that has competitive advantage. It means that they are ready to do business by following the model of a true businessman figure, our prophet Muhammad saw. It is hoped that young Indonesians can develop the Indonesian economy by applying business management that had been applied by the prophet Muhammad saw. It has been proved that his management principle that he did was accurate and reliable that made his business form always get profit and never loss.